2002
DOI: 10.1530/eje.0.1460339
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex steroids in the regulation of insulin sensitivity and serum lipid concentrations during male puberty: a prospective study with a P450-aromatase inhibitor

Abstract: Objective: Our purpose was to study the sex steroid-mediated changes in serum insulin and lipid concentrations in boys during puberty. Design and Methods: We treated boys with constitutional delay of puberty either with testosterone plus placebo or with testosterone plus an aromatase inhibitor, letrozole, which inhibits the conversion of androgens to oestrogens. We demonstrated previously that during treatment with testosterone plus letrozole the increase in testosterone concentration was more than 5-fold high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
7
28
0
Order By: Relevance
“…Recent studies by Dunkel and co-workers [6][7][8] in Finland showed results generally consistent with our observations. The authors compared the effect of letrozole plus testosterone to testosterone alone in treating boys with delayed puberty.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recent studies by Dunkel and co-workers [6][7][8] in Finland showed results generally consistent with our observations. The authors compared the effect of letrozole plus testosterone to testosterone alone in treating boys with delayed puberty.…”
Section: Discussionsupporting
confidence: 93%
“…5 To date, a couple of studies, at least in the short term, indicate that the use of an AI is safe and promising. [6][7][8] …”
mentioning
confidence: 99%
“…Letrozole reduced the fasting insulin levels and decreased high density lipoprotein (HDL) cholesterol. It remained unclear whether the reduction in HDL was related to the excessive rise in serum testosterone or to the reduction in E 2 that occurred in the letrozole-treated group (28). In adult men, most experience has been gained with anastrozole.…”
Section: Discussionmentioning
confidence: 99%
“…Although only short-term follow-up is still available, these controlled clinical trials have provided a good safety profile for treatment with aromatase inhibitors. No adverse effects have been demonstrated on glucose, plasma lipid concentrations, and insulin sensitivity (20,23), spermatogenesis (24), and cognitive function (25). Additionally, aromatase inhibitors did not induce detrimental effects on bone mineral density (19,20,26).…”
Section: Discussionmentioning
confidence: 93%